Development of rule-based eye-hand-decoupling in children and adolescents. Issue 8 (17th November 2019) - Dalecki, Marc; Gorbet, Diana J.; Sergio, Lauren E.
ABSTRACT: In the present study, we characterize how the ability to decouple guiding visual information from a motor action emerges during childhood and adolescence. Sixty-two participants (age range 8–15 yrs.) completed two eye-hand coordination tasks. In a direct interaction task, vision and motor action were in alignment, and participants slid their finger along a vertical touch screen to move a cursor from a central target to one of four peripheral targets. In an eye-hand-decoupled task, eye and hand movements were made in different planes and cursor feedback was 180° reversed. We analyzed whether movement planning, timing and trajectory variables differed across age in both task conditions. There were no significant relationships between age and any movement planning, timing, or execution variables in the direct interaction task. In contrast, in the eye-hand-decoupled task, we found a relationship between age and several movement planning and timing variables. In adolescents (13–15 yrs.), movement planning and timing was significantly shorter than that of young children (8–10 yrs.). Eye-hand-decoupled maturation emerged mainly during late childhood (11–12 yrs.). Notably, we detected performance differences between young children and adolescents exclusively during the eye-hand decoupling task which required the integration of rule-based cognitive information into the motor action. Differences were not observed during the direct interaction task. Our results quantify an important milestone for eye-hand-decoupling development in late childhood, leading to improved rule-based motor performance in early adolescence. This eye-hand-decoupling development may be due to frontal lobe development linked to rule-based behavior and the strengthening of fronto-parietal networks.